A solution and solid state study of vanadium complexes - Pretorius, Carla (University of the Free State, 2014)
Vanadium is an early first-row transition metal that is known for the beautiful coloured compounds that it forms in a wide range of oxidation states. In high oxidation states, vanadium is very oxophilic whilst at low oxidation states, π-donating ligands are preferred. It is the only element in the periodic table to be named after a goddess (the Nordic goddess Vanadis), and perhaps with this legacy in mind some unpredictable and surprising chemistry might be expected. This research study focussed on the rich and diverse coordination chemistry of vanadium. Various vanadium(IV) and vanadium(V) compounds were successfully synthesized with O,O and N,O-Bid ligand systems (Bid= five or six membered chelating ligand via O,O’ or N,O-donor atoms). These ligands were chosen for their wide application in terms of industrial use in the development of catalysts as well as their biological activity for pharmacological application. To achieve the above mentioned aim various characterization techniques were mastered such as IR, UV/Vis, NMR and single crystal X-ray diffraction. To this regard four vanadium complexes were successfully characterized by XRD namely [VO(dbm)2], [VO(dbm)2(MeOH)]•2MeOH, [VO(dbm)2py] and (C9H17O2)[VO2(cupf)2]. The three diketonato containing complexes provided unique stereo-electronic changes in each case and the effect upon distortion of the vanadium centre as well as the trans effect of the oxido bond could be evaluated. The last mentioned compound was of special interest as the novel 2,2,6,6- tetramethyldihydropyran-4-onium that acts as cation for the anionic vanadium complex was speculated to have formed either by cyclization of acetone during the reaction or by action of the vanadium present. In addition to the synthesis component of the research a kinetic substitution study was instigated. The complex solution chemistry of vanadium resulted in a wide array of experiments to evaluate the effects of not only ligand concentration on reaction rates but also pH dependence of certain species in solution. This culminated in a proposed reaction mechanism and rate law that accounts for various pH, pKa and concentration effects. As vanadium is known for its biological activity, selected complexes synthesized from this study was investigated for in vitro cancer screening. These results were concluded as not being positive but provided valuable insight for future ligand and complex design. 51V NMR was effectively used in this study both in the synthesis component as well as the kinetic study conducted. Valuable insight into the electronic environment experienced by the vanadium centre was obtained and correlations could be established between steric strain within a complex and the amount of shielding experienced by the vanadium centre. Additionally, experiments such as in the kinetic study could be followed over time on 51V NMR and revealed important information regarding product formation and the identification of an intermediate [VO(O2)(2,3-dipic)]2- in the reaction which was vital in construction of the reaction mechanism.

Vanadium is `n vroeg eerste ry oorgangsmetaal wat bekend is vir die pragtige gekleurde komplekse wat dit vorm in `n wye reeks oksidasietoestande. In `n hoë oksidasietoestand is vanadium baie oksofilies terwyl π-skenkende ligande verkies word by lae oksidasietoestande. Dit is die enigste element wat na `n godin vernoem is (die Noordiese Vanadis), en bring dalk saam met hierdie erfenis `n gevoel van onvoorspelbare en verrassende chemie. Hierdie navorsingstudie fokus op die ryk en uiteenlopende koördinasiechemie van vanadium. Verskeie vanadium(IV) en vanadium(V) komplekse is suksesvol vervaardig met O,O en N,O-Bid ligandstelsels (Bid= vyf-of seslid chelerende ligande via ‘n O,O’-of N,O-donerende paar). Hierdie ligande is gekies vir hulle wye verskeidenheid gebruike in terme van industriële toepassings in die ontwikkeling van kataliste asook hulle biologiese aktiwiteit vir farmakologiese toepassing. Om die bogenoemde doel te behaal is verskeie tegnieke, soos IR, UV/Vis, KMR en enkelkristal X-straaldiffraksie, bemeester. In hierdie verband is vier vanadium komplekse suksesvol gekarakteriseer deur XRD, naamlik [VO(dbm)2], [VO(dbm)2(MeOH)]•2MeOH, [VO(dbm)2py] en (C9H17O2)[VO2(cupf)2]. Die drie diketonato-bevattende komplekse het in elke geval unieke stereo-elektroniese veranderinge geopenbaar en die effek van vervorming van die vanadiumkern asook die trans effek van die oksido binding kon nagevors word. Die laasgenoemde kompleks is van spesiale belang aangesien gespekuleer word dat die unieke 2,2,6,6, tetrametielpironium wat optree as katioon vir die anioniese vanadium kompleks gevorm is òf deur siklisering van asetoon gedurende die reaksie, òf deur die aksie van die vanadium teenwoordig. Byvoegend tot die sintetiese aspek van hierdie projek is `n studie van `n kinetiese substitusie geïnisieer. Die ingewikkelde oplossingschemie van vanadium het gelei tot `n wye reeks eksperimente om nie net die effek van ligand konsentrasie op reaksietempo nie, maar ook pH-afhanklikheid van sekere spesies in oplossing vas te stel. Dit het uitgeloop op die voorgestelde reaksiemeganisme en tempowet wat verskillende pH, pKa en konsentrasie effekte in ag neem. Aangesien vanadium bekend is vir biologiese aktiwiteit is gekose komplekse wat vir hierdie studie vervaardig is ondersoek vir in vitro kanker sifting. Hierdie resultate is gevind as nie positief nie, maar het waardevolle insigte verskaf ten opsigte van toekomstige ligand- en kompleksontwerpe. 51V KMR is effektief in hierdie studie gebruik in beide die sintetiese komponent en die kinetiese studie en waardevolle inligting is ingewin aangaande die elektroniese omgewing wat deur die vanadium kern ervaar word. Korrelasies kon vasgestel word tussen die steriese stremming binne die kompleks en die hoeveelheid skerming deur die vanadium kern ervaar. Daarbenewens kon eksperimente soos die kinetiese studie oor `n tydperk gevolg word wat belangrike inligting verskaf het aangaande produkvorming en die identifikasie van intermediêre die [VO(O2)(2,3-dipic)]2-, wat uiters belangrik was in die konstruksie van die reaksiemeganisme.
Dissertation (M.Sc. (Chemistry))--University of the Free State, 2012
Keywords: Vanadium; Ligands